Special education teachers’ for autism spectrum disorder children: behavioral intention and use of technology in Malaysia - Khan, Mohammad Shadab; Mohamadali, Noor Azizah; Shah, Asadullah (Persatuan Sistem Maklumat Malaysia (MyAIS), 2021)
The fundamentals of Sustainable development goals (SDG’s) for humanity is developed on the principle of “leaving no one behind” This holistic approach constitutes the pillar for ‘Quality education’ with inclusion. Special education ensures development and progress through inclusion in mainstream education. This research aims to identify critical indicators that hinder teachers from adopting technological intervention in special education for children with Autism spectrum disorder (ASD)—focusing on the factors which influence their behavioral intention and use of technology. The research gap between the teachers’ behavioral intention and technology use is not yet studied within the Malaysian special needs education context for children with ASD. Unified Theory of Acceptance and Use of Technology 2 model (UTAUT 2) is used to explore the factors that impact behavioral intention and technology use among special education teachers for ASD children. The developed hypothesis will be tested later through a survey, questionnaire, and analysis using the statistical package for social science (SPSS). This research will help identify the barriers and critical motivating factors of technology adoption among the special education teachers for ASD and their behavioral intention in the Malaysian context, which will help educators with clear guidelines to enhance teaching quality by redefining roles.